Pengaruh Model Pembelajaran Think Talk Write (TTW) Terhadap Kemampuan Menulis Teks Eksplanasi Siswa Kelas VI - Rosul Latifah, Sunarti; Sholehuddin (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research is motivated by the low ability of students in learning to write explanatory texts. This research aims to determine the effect of Think Talk Write (TTW) learning model on the writing ability of explanatory texts for sixth grade students at SDN Pamulang Indah. The research method used is quantitative with a quasi-experimental design (non-equivalent control group design) with a population of 4 classes and a sample of 2 classes, namely the experimental class and the control class. Data collection techniques in this study include observation and giving tests in the form of initial tests (pretest) and final tests (posttest). Data analysis technique using normality test, homogeneity test, hypothesis test (t-test) and n-gain. The research results obtained that, the writing ability of explanatory texts for students using the Think Talk Write (TTW) learning model based on the t-test table can be seen that the significance is 0.000 < 0.05, meaning H0 is rejected and Ha is accepted, meaning there is an average difference between the experimental class or the control class, there is a significant difference in writing skills for the experimental and control classes. Based on the results of the N-Gain score test, it shows that the average N-Gain score for the experimental class who learned using the Think Talk Write (TTW) learning model increased by 72.639 or 72.63% which is included in the high category or with a minimum n-gain score of 54% and a maximum of 100%. Therefore, it can be concluded that the use of the Think Talk Write (TTW) learning model has a significant effect on the writing ability of explanatory texts for sixth grade students at SDN Pamulang Indah.